PENGEMBANGAN BAHAN AJAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA SUB TEMA PEMANFAATAN ENERGI DI KELAS IV SD - Firman Firman; Hendra Budiono (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2020)
Abstract The purpose of this study was to obtain valid, practical and efficient teaching materials using the Problem Based Learning model on the sub-theme of energy use in the fourth grade of elementary schools. This research utilized research and development method with a model of development of the 4-D (Four D) consisting of four stages: define, design, development, and the disseminate. The results of this study obtained an average general validation result in 3.38 with very valid categories. The practicality test was seen from the implementation of the Problem Based Learning model in learning with an average of 3.44, the practical category, the student response questionnaire obtained a practical level in 3.49 with the practical category. The effectiveness test seen from student activities during the learning process includes visual, oral, motor, mental, and emotional activities showing an average overall activity of 79.58 in the High category. From this research it can be concluded that the teaching materials developed are valid, practical, and effective.   Abstrak   Tujuan penelitian ini adalah untuk mendapatkan bahan ajar yang valid, praktis dan efisien menggunakan model Problem Based Learning pada sub tema pemanfaatan energi di kelas IV SD. Penelitian ini adalah penelitian pengembangan (research and development) dengan model pengembangan 4-D (Four D) yang terdiri dari empat tahap yaitu pendefenisian (define), perancangan (design), pengembangan (develop), dan penyebaran (disseminate). Hasil penelitian ini didapat rata-rata hasil validasi secara umum 3,38 dengan kategori sangat valid. Uji praktikalitas dilihat dari keterlaksanaan model Problem Based Learning dalam pembelajaran dengan rata-rata 3,44, kategori Praktis, angket respon siswa didapat tingkat kepraktisan 3,49 dengan kategori praktis. Uji efektivitas dilihat dari aktivitas siswa selama proses pembelajaran meliputi aktivitas visual, oral, motor, mental, dan emosional menunjukkan rata-rata aktivitas keseluruhan 79,58 dengan kategori Tinggi. Dari penelitian ini dapat disimpulkan bahwa bahan ajar yang dikembangkan berada pada kriteria valid, praktis, dan efektif.